First Overview of Zoological Medicine on Iberian Countries - Fábio Cardoso-Freitas; Vanessa Silva; Albert Martinez-Silvestre; Ângela Martins; Patrícia Poeta (Veterinary Sciences, 2024)
The role of veterinary doctors, particularly those dedicated to Zoological Medicine, is becoming increasingly relevant and essential within the One Health framework. Educational and employment opportunities in this field vary widely across Europe, prompting us to characterise the sector in Portugal and Spain. A survey was conducted, resulting in 169 valid responses from veterinarians. Respondents were characterised based on gender, age, work environment, the highest level of education, additional training, whether they attended zoological medicine classes at university and their perception of the adequacy of that training. Further factors included years of experience, the percentage of their work involving zoological medicine, sectors they work in, the types of animals they treat, their confidence in treating these animals, sources of information they use, and membership in relevant professional associations. Relationships between these variables were examined. The results describe Iberian professionals working with non-traditional pets, wildlife, and zoo animals. Notably, only half of these professionals had taken zoological medicine classes at university; among those, the majority felt they inadequately prepared them for their work. Given the findings, enhancing the training and resources available to these professionals is crucial to prepare them for their roles better.